Optimal WAMS configuration in nordic power system - Hassan, Mohamed A. M.; Abdalla, Omar H.; Fayek, Hady H.; Hassan Abdalla Hashim, Aisha; Toha, Siti Fauziah (IJCSNS, 2023)
The Smart grids are considered as multi-disciplinary power systems where the communication networks are highly employed. This paper presents optimal wide area measurement system (WAMS) configuration in Nordic power system. The transition from SCADA to WAMS becomes now trend in all power systems to ensure higher reliability and data visibility. The optimization applied in this research considered the geographical regions of the Nordic power system. The research considered all the devices of WAMS namely phasor measurement units (PMUs), phasor data concentrators (PDCs) and communication links. The study also presents two scenarios for optimal WAMS namely base case and N-1 contingency as different operating conditions. The result of this research presents technical and financial results for WAMS configuration in a real power system. The optimization results are performed using MATLAB 2017a software application.